A Review On The Implementation Of Picture Series In Teaching Writing Skills - Agung Wibowo, Rahmat; Darmawan, Darmawan; Kusuma Dewi, Anjar; Mashuri, Mashuri (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This library research reviews recent studies on the use of picture series to improve students’ writing skills in English as a Foreign Language (EFL) classrooms. Writing is often difficult for students because they have trouble finding ideas, organizing sentences, and using correct grammar. Many teachers and researchers have tried different ways to help students write better. One popular technique is using picture series as visual aids. This study collected data from five recent articles published between 2019 and 2024. The reviewed studies used different methods, including experimental research, classroom action research, and qualitative reviews. All studies reported positive results. Students who learned writing through picture series were more motivated, could organize their ideas better, and wrote more creatively. Even students with low English skills improved when teachers used pictures to support their writing. However, some teachers reported challenges, such as preparing good picture materials and managing large classes during picture-based activities. Despite these challenges, the findings strongly suggest that picture series are an effective and engaging tool for teaching writing. They help students become more confident and reduce the fear of writing in English. This research recommends that teachers use picture series more often, especially in EFL contexts, and that future studies explore digital picture tools to make this technique even more practical in modern classrooms.